2010
DOI: 10.1007/s00107-010-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel façade sandwich panel with low-density wood fibres core and wood-based panels as faces

Abstract: Abstract. The paper explores, experimentally and theoretically, the possibility of producing a novel cladding sandwich panel comprised of a low-density wood fibre (WF) core and faces made of wood-based panels.Tests on small specimens, using physical and optical devices, were performed for the basic mechanical characterization of WF. Shear modulus (G) was the main target; and values for a range of nominal densities (ρ) from 110 to 190 kg/m 3 were obtained.Short term load tests on real scale WF sandwich (WFS) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Aluminum and steel sheets are generally preferred among metals as face materials. Wood‐based face sheets are also being used in sandwich structures along with wood‐fiber cores because of good thermal and acoustic insulation properties . However, with recent breakthroughs in hybrid materials, functionally graded materials (FGMs) have overtaken conventional materials.…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…Aluminum and steel sheets are generally preferred among metals as face materials. Wood‐based face sheets are also being used in sandwich structures along with wood‐fiber cores because of good thermal and acoustic insulation properties . However, with recent breakthroughs in hybrid materials, functionally graded materials (FGMs) have overtaken conventional materials.…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…Tagarielli et al [30] revealed that the axial compression properties of balsa wood are highly strain-rate sensitive, providing a significant increase in dynamic strength compared with quasi-static behaviour, and the material's axial compression properties have been shown to be clearly superior to those of polyvinyl chloride (PVC) foams of comparable densities. Fernandez-Cado et al [31] designed wood-based sandwich panels to withstand their self-weight and wind load, and thus avoid the question of creep. Kepler [32] investigated a concept for improving the shear stiffness properties of balsa core material for sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental research on wood-based sandwich panels is performed by Kawasaki et al [6,7] and Fernandez-Cabo et al [8] employing low-density fiber board as a core material. In the recent study of Mohamed et al [9], mechanical and thermal properties of structural insulated panels with oriented strand board (OSB) and GFRP skins were investigated.…”
Section: Introductionmentioning
confidence: 99%